Comparison of Effectiveness of Manual Therapy for Infant Crying: systematic review and meta-analysis of randomized controlled trials - Ui Jin Park; Hye In Jeong; Kyeong Han Kim (Journal of Pharmacopuncture, 2023)
Objectives: The aim of this systematic review and meta-analysis is to assess and compare the effectiveness of manual therapy in alleviating infant crying, a common symptom of nocturnal crying (NC) and infantile colic (IC). Methods: Total effective rate, crying time and adverse events were used as outcome indicators. To assess the quality, the risk of bias was determined for each study by two authors, using the Cochrane Collaboration's risk of bias tool. RevMan 5.0 was used for data analysis. A total of 98 articles were identified from 6 electronic databases. Results: Among them, twenty-seven studies which included 13 NC and 14 IC were included. Meta-analysis showed favorable effects tuina therapy on total effective rate (TER) of NC (RR: 1.20 [95% CI 1.05 to 1.37], p = 0.007), chiropractic therapy on crying time change of IC (SMD: -0.83 [95% CI -1.61 to -0.06], p = 0.04) and massage on total crying time of IC (SMD: -0.86 [95% CI -1.09 to -0.63], p < 0.00001). This systematic review compares different manual therapies for the treatment of NC and IC. While tuina, chiropractic, and massage show results in alleviating symptoms, the overall evidence remains limited due to the low quality and heterogeneity of the included studies. Conclusion: Therefore, further high-quality research with unified control groups is needed to establish manual therapy as a recommended treatment option for NC and IC. Protocol registration number is CRD42022348143 01/08/2022.